An analysis of decentralized finance toward investor attention and financial asset performance - Foo, Shi Lun (2024)
As part of the requirements for earning a Bachelor of Economics (Hons) in Global Economics, this research is being turned in. "An analysis of decentralized finance toward investor attention and financial assets performance " is the title of this study. The research will be conducted using EViews 12 to shows the relationship between variable social sentiment on DeFi market capitalization will be test using Google trend as the main independent and 3 control variable , trading volume , active address , crypto volatility index by using Monthly data from April 2019 to February 2024 total of 59 Month . Next for panel data analysis, we will using ROE , NIM and ROA of bank in United State as dependent , and with 1 independent Defi( measure with TVL ) , 4 control variable such as NPL , TA , OPX and CA by conducting Quarterly data from 2018Q3 - 2023Q4